Spatial variation of reference crop evapotranspiration on Tibetan Plateau - Yong-hong Yang (Water Science and Engineering, 2009)
This study is based on meteorological observation data collected at 38 weather stations on the Tibetan Plateau over several decades. Daily reference crop evapotranspiration (ET0) was calculated with the FAO-56 standard Penman-Monteith formula. A test of normality was performed with Statistica 6.0 software, isotropic and anisotropic semi-variogram analysis was conducted with the GS+ (geostatistics for the environmental sciences) system for Windows 7.0, and the characteristics of spatial variation of daily ET0 were obtained. The following results can be obtained: Daily ET0 for different periods on the Tibetan Plateau are distributed normally; Except for daily ET0 in the E-W (east-west) direction in the summer, which showed a slight negative correlation with distance change, the Moran's indexes of daily ET0 for different periods in all directions on the Tibetan Plateau within a 100-km distance were positive, demonstrating a positive correlation with distance change; Variograms of daily ET0 in June, the dry season, the wet season, as well as annual average daily ET0 fit well with the Gaussian model; A variogram of daily ET0 in December fit well with the exponential model; Variograms of daily ET0 for the four seasons fit well with the linear with sill model.